Evidence for non-Dzyaloshinskii-Moriya ferromagnetism in epitaxial BiFeO3 films - Prokhorov, V.G.; Nikolaenko, Yu.M.; Levtchenko, G.G.; Svetchnikov, V.L.; Lee, Y.P.; Park, J.S.; Eom, T.W.; Kim, J.M.; Kaminsky, G.G.; Khokhlov, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
BiFeO3 films have been prepared by dc magnetron sputtering on LaAlO3 (001) single-crystalline substrate. X-ray diffraction analysis and high-resolution electron-microscopy study reveal that the films have a highly coriented orthorhombic crystal structure. It was found that the magnetic properties of the BiFeO3 films are typical for the ensemble of interacting superparamagnetic clusters rather than for the Dzyaloshinskii–Moriya weak ferromagnet. Appearance of the extrinsic nanoscale superparamagnetic clusters is explained by the oxygen deficiency in certain regions of the film, where the ferromagnetic ordering is realized through the double-exchange mechanism by Zener.